A cognitive semantic analysis of cancer metaphor in Malay and English women’s narratives - Mohd Jamil, Nur Sabrina Zafiran (2019)
Metaphor on cancer has been frequently addressed in research due to its powerful use in both spoken and written discourse. The analysis of cancer related metaphor in language would provide insights into how cancer patients conceive the cancer disease and their experiences with the disease. However, studies conducted cross- linguistically on cancer metaphors are scarce as most previous studies on cancer have mainly focused on European languages. This study sought to examine the use of cancer related metaphors in women’s narratives in Malay and English language. The specific objectives of this study are to unravel the conceptual metaphor that underlie the metaphorical expressions in Malay women’s narratives on cancer experience and to compare the unravelled Malay conceptual metaphor with those of English.